2022
DOI: 10.11622/smedj.2020140
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of septic arthritis in childhood: a 16-year experience and review of literature

Abstract: INTRODUCTION Septic arthritis (SA) is a devastating infection with a high rate of sequelae. The aim of this retrospective study was to determine the epidemiology, clinically significant sequelae and risk factors for developing these sequelae in children admitted to our hospital with SA. METHODS Patients with bacteriologically and/or radiologically confirmed SA from January 1999 to December 2014 were identified from discharge and laboratory records. Data was collected through a retrospective review of the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…We agree with the view of previous studies that THA must be performed in infected hips that had remained quiescent for more than 10 years to prevent a higher risk of reinfection of previous pyogenic infections after THA [ 1 , 10 ]. Thus, we performed preoperative assessments to exclude evidence of persistent infection.…”
Section: Methodssupporting
confidence: 92%
“…We agree with the view of previous studies that THA must be performed in infected hips that had remained quiescent for more than 10 years to prevent a higher risk of reinfection of previous pyogenic infections after THA [ 1 , 10 ]. Thus, we performed preoperative assessments to exclude evidence of persistent infection.…”
Section: Methodssupporting
confidence: 92%
“…Previous studies have shown that 10–17% of patients with SA experienced sequelae 4 . Similarly, in this study, six patients (16%) experienced chronic sequelae.…”
Section: Discussionsupporting
confidence: 80%
“…The associated mild symptoms and limited increase in the levels of acute‐phase reactants create problems, and it is difficult to isolate 5 . Thus, the bacterium can be more easily identified using aerobic blood culture vials or real‐time PCR assays 4 . Notably, patients with unknown pathogens in this study were mostly between 2 and 5 years old ( P < 0.05).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nosocomial infections are mostly due to gram negative organisms [ 5 ]. In a retrospective review by Jeyanthi et al that included six neonates, methicillin resistant Staphylococcus aureus was the predominant organism [ 6 ]. In the neonatal and the broader paediatric group, Klebsiella pneumoniae , Staphylococcus aureus and Escherichia coli are the commonest organisms.…”
Section: Discussionmentioning
confidence: 99%